Via placement optimization for a group of wires - Knop, K. A.; Luzin, S. Yu. (Technology and design in electronic equipment, 2015)
Most PCB design CAD systems offer a limited number of “patterns” for the via placement on a bus (group of wires) which would be either a single- or a double-row placement. This article demonstrates the incorrectness of such limitations, because in this case the mounting space is used not in an optimal way. The paper presents the optimum solution for a certain type of problems on via placement when changing the layer of a bus. The solution suggests a regular (periodic) arrangement, but with a multi-row placement. The calculation of the parameters for optimal placement is narrowed, in general, to finding the number of via rows with which the area of a topological fragment is minimal.